Prove the identity:
(sec A-cos A).(cot A+tan A)=sec A.tanA

 LHS = (secA-cosA) * (cotA+tanA) 
= (1/cosA - cosA) * (cosA/sinA + sinA/cosA) 
= (1 - cos^2 A)/cosA * ((sin^2 A +cos^2 A) / sinAcosA) 
= ((sin^2 A) / cosA) * ( 1 / sinAcosA) 
= sinA / cos^2 A = (sinA/cosA) * (1/cosA) = tanA * secA = RHS

  • 6
LHS : ( secA - cosA) . (cotA+ tanA)
          (1/ cosA - cosA) .( cosA/ sinA + sinA/cosA)
          (1- cos2A /cosA). (cos2A +sin2A/ sinAcosA)
​          (sin2A / cosA ) .(1/ sinA/cosA)
           (sinA/cosA) . (1/cosA)
​          tanA . secA       =RHS                              (proved)
cheers!
  • 5
What are you looking for?